2021
DOI: 10.3390/e23060786
|View full text |Cite
|
Sign up to set email alerts
|

Are Mobility and COVID-19 Related? A Dynamic Analysis for Portuguese Districts

Abstract: In this research work, we propose to assess the dynamic correlation between different mobility indices, measured on a daily basis, and the new cases of COVID-19 in the different Portuguese districts. The analysis is based on global correlation measures, which capture linear and non-linear relationships in time series, in a robust and dynamic way, in a period without significant changes of non-pharmacological measures. The results show that mobility in retail and recreation, grocery and pharmacy, and public tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…Those more detailed results are provided in Appendix B . This closer look reveals a wide variation in locations included in this research, including one global study that also specifically addressed the regions of Africa, Latin America, and the Caribbean [ 35 ], and country-specific studies of England [ 31 ], India [ 34 ], Portugal [ 29 ], Turkey [ 32 ], and the US [ 30 , 33 ]. As previously noted, all studies used Google community mobility data that provided aggregated mobility scores for six sets of destinations: retail and recreation, grocery and pharmacy, parks, transit stations, workplaces, and residential destinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those more detailed results are provided in Appendix B . This closer look reveals a wide variation in locations included in this research, including one global study that also specifically addressed the regions of Africa, Latin America, and the Caribbean [ 35 ], and country-specific studies of England [ 31 ], India [ 34 ], Portugal [ 29 ], Turkey [ 32 ], and the US [ 30 , 33 ]. As previously noted, all studies used Google community mobility data that provided aggregated mobility scores for six sets of destinations: retail and recreation, grocery and pharmacy, parks, transit stations, workplaces, and residential destinations.…”
Section: Resultsmentioning
confidence: 99%
“…The strong indication here is that park use helped to lower COVID-19 incidence insofar as it served to replace other forms of mobility that may have been riskier. While no other studies directly looked at park mobility as a replacement for other forms of mobility, two studies noted that while park mobility was associated with worse COVID-19 numbers, the association was lower for parks than for other mobility destinations [ 29 , 33 ], and two studies found no association between park mobility and COVID-19, while associations did exist for other mobility factors [ 30 , 34 ]. What emerges then is the strong suggestion that mobility in general increases risk, but park mobility is relatively safer and has lower negative outcomes than other forms of mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus crisis has led to unusual mobility restrictions in recent years [8,9]. The analysis carried out in this paper is within a pre-COVID-19 framework.…”
Section: Tourism Sector Gross Domestic Product and Randomness In Decision-makingmentioning
confidence: 99%
“…In order to quantify and qualify the degree of social distancing and its effects, some different approaches have been proposed: by survey questionnaires in the population in order to assess adherence to social distancing and to compare it to the growth of cases, or deaths [12], or by using mobility data from different sources [1319]. In the latter case, a mobility or social distancing metric is compared to the growth rate of cases (or deaths) of COVID-19, or to the effective reproduction number R t .…”
Section: Introductionmentioning
confidence: 99%